PERANCANGAN SISTEM APLIKASI ABSENSI MENGGUNAKAN FACE RECOGNITION DAN LOKASI BERBASIS ANDROID PADA PT. TRANS CORP FOOD AND BEVERAGE - Indrajit Sumarsono; Kecitaan Harefa (Shofanah Media Berkah, 2023)
This study focuses make it easier for employees to do attendance, assist HRD in managing employee attendance data and can see in real time. This attendance system was developed using facial recognition technology (Face Recognition) and utilizing GPS (Global Positioning System) can automatically check the location of employee absences. So that employees are actually in the office, they use a radius of 20 meters from the company's location point. The methodology used in the design of the attendance system using the SLDC method with the Waterfall and facial recognition using the Eigenface. The results of this study indicate that the face tilt test for face recognition has an accuracy rate of 88.88%, a facial distance test with an object has an accuracy rate of 83.33%, a light intensity test has an accuracy rate of 75%, an accuracy rate of 91.66% for testing using additional accessories, and an attendance test performed by employees has a high accuracy rate. 100%, attendance testing within an absent radius of 20 meters from the company's location point has a 100% accuracy rate, and attendance testing outside an absent radius of 20 meters from the company's location point has a 100% accuracy rate. From the test results, it can be concluded that if the face tilt is facing upwards of 300, the use of additional accessories such as masks, the distance between the face and the object is 200 meters, and if the light intensity is dark, the face cannot be recognized.